RESEARCH ON THE HEAVY METAL CONTENT IN ONION BULBS CORRELATED WITH SOIL FROM PRIVATE HOUSEHOLDS LOCATED IN THE COPŞA MICĂ AREA, CENTRAL ROMANIA - Bogdan Ştefan OPREA; Dumitru-Marian MOTELICĂ; Nicoleta Olimpia VRÎNCEANU; Mihaela COSTEA; Georgiana Iuliana PLOPEANU; Vera CARABULEA (Journal of Applied Life Sciences and Environment)
Food safety and the high demand for food have represented worrisome problems worldwide in recent decades. It is well known that plants can accumulate metals from contaminated soil and through deposits from pollutant emissions released by contaminated sources. Cadmium, copper, zinc, and lead are poisonous elements. The accumulation of heavy metals in plants grown in polluted areas represents a major risk to human and animal health. Soil pollution with heavy metals is a global problem that has an unfavourable impact on the environment. For this study, data collected from 65 individual households located in the Copşa Mică area were used to estimate the bioaccumulation of four different heavy metals [cadmium (Cd), lead (Pb), zinc (Zn), and copper (Cu)] in onion bulbs in different scenarios, in correlation with the total metal content from the soil. The highest correlation coefficients were obtained for the regression curves established for the estimation of Cd (r = 0.648***), Zn (r = 0.592***), and Pb (r = 0.525***) in onion bulbs. In the case of copper (Cu), the linear correlation coefficient was insignificant (r = 0.088ns). The mean cadmium and lead values determined in the onion samples from the study area did not exceed the maximum stable levels for these contaminants in vegetables.